First-Principles Study of Van Der Waals Interactions between Halogen Molecules (Cl2 and I2) (Journal of Nepal Physical Society, 2019)
Density Functional Theory (DFT) based first-principles calculations have been performed to investigate vander Waals (vdW) interactions in between halogen atoms/molecules —Cl-Cl, I-I, Cl2-Cl2, Cl2-I2, I2-I2—via with and without a non-local exchange-correlation (XC) functional (vdW-DF) using Quantum ESPRESSO codes. The non-polar covalent bond length between atomic halogens (Cl-Cl and I-I) is not observed to be affected by vdW interactions and agrees well with experimental values. The binding energy between theatomic halogens, on the other hand, is slightly corrected by vdW interactions. However, the role of vdW interactions is observed to be crucial to bind molecular halogens. The molecules are weakly bound in the presence of vdW interactions and not correlated (bound) in the absence of them.